2012
DOI: 10.1007/s00011-012-0514-y
|View full text |Cite
|
Sign up to set email alerts
|

Different inflammatory stimuli in the footpad of mice influence the kinetics of resident peritoneal cells

Abstract: These data show that cells from the peritoneal cavity are influenced by pathologies in remote regions of the animal. How this novel phenomenon influences overall immune responses, courses of infection and tumor growth are open to further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…However, CD8 + T cells decreased in the peritoneal cavity, suggesting their migration to the site of pathogen proliferation. This finding is in corroboration to previous studies that have already shown cells in the peritoneal cavity to migrate to other sites (Almeida et al, 2001; Palos et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…However, CD8 + T cells decreased in the peritoneal cavity, suggesting their migration to the site of pathogen proliferation. This finding is in corroboration to previous studies that have already shown cells in the peritoneal cavity to migrate to other sites (Almeida et al, 2001; Palos et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…These researchers described a macrophage cell trafficking pathway, that is, the migration of these cells from the peritoneal cavity to a tumour lesion; they demonstrated that in rats subcutaneously inoculated with AK‐5 tumour cells, an influx of immune cells occurs in the peritoneal cavity, with hyperactivation of macrophages and elevated levels of cytokines, NO and O 2 − . Other studies have demonstrated the migration of peritoneal cells to other tissues . In this context, we can infer that our results concerning total and differential numbers of peritoneal lavage cells appear to reflect the changes observed in the footpad with a significant increase in the total number of cells recovered by peritoneal lavage during the infectious process, particularly at 8 months postinoculation compared to control animals.…”
Section: Discussionsupporting
confidence: 72%
“…At 60 days post-infection, necrosis had started to progress in L. major infection (Figure B,C). A positive control of inflammation was also analyzed by injecting LPS into the footpad dermis of another set of animals …”
Section: Resultsmentioning
confidence: 99%